ANALISIS KURIKULUM PONDOK PESANTREN MODERN: SEBAGAI MODEL PENDIDIKAN TERPADU ANTARA PESANTREN DAN SEKOLAH FORMAL - Nur Aina (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to analyze the curriculum of modern Islamic boarding schools (pesantren) as an integrated educational model combining traditional pesantren education with formal schooling. Modern pesantren not only preserve classical Islamic traditions such as the study of classical Islamic texts (kitab kuning), character building, and spiritual development, but also adopt the national curriculum covering general subjects, science, and technology. This research employs a qualitative approach using library research and descriptive analysis methods. The findings indicate that curriculum integration in modern pesantren creates a balance between religious and general knowledge, character formation, and the development of 21st-century skills. This model contributes to producing graduates who possess academic competence, spiritual depth, and readiness to face global challenges. Therefore, the modern pesantren curriculum can serve as an alternative integrated educational model relevant to the national education system.